2018
DOI: 10.1039/c8nj01932k
|View full text |Cite
|
Sign up to set email alerts
|

A ligand strategic approach with Cu-MOF for enhanced solar light photocatalysis

Abstract: A bi-linker approach was employed on Cu-MOF for enhanced solar-light photocatalytic activity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…On the other hand, IR spectra of these modified Cu meshes were collected, and are displayed in Figure 4b. In comparison to the pristine Cu mesh, these modified Cu meshes showed a number of bands at 700~1850 cm −1 , which were characteristic peaks of the carboxylate ligands, as displayed in Figure S2 [31][32][33]. In particular, the bands at 734 and 1500 cm −1 can be ascribed to aromatic rings [31], whereas the bands at 1400 cm −1 , as well as 1670 cm −1 , correspond to the coordinated carboxylic, and carbonyl groups in BDC-based MOF.…”
Section: Characterization Of Cucf Meshesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, IR spectra of these modified Cu meshes were collected, and are displayed in Figure 4b. In comparison to the pristine Cu mesh, these modified Cu meshes showed a number of bands at 700~1850 cm −1 , which were characteristic peaks of the carboxylate ligands, as displayed in Figure S2 [31][32][33]. In particular, the bands at 734 and 1500 cm −1 can be ascribed to aromatic rings [31], whereas the bands at 1400 cm −1 , as well as 1670 cm −1 , correspond to the coordinated carboxylic, and carbonyl groups in BDC-based MOF.…”
Section: Characterization Of Cucf Meshesmentioning
confidence: 99%
“…In comparison to the pristine Cu mesh, these modified Cu meshes showed a number of bands at 700~1850 cm −1 , which were characteristic peaks of the carboxylate ligands, as displayed in Figure S2 [31][32][33]. In particular, the bands at 734 and 1500 cm −1 can be ascribed to aromatic rings [31], whereas the bands at 1400 cm −1 , as well as 1670 cm −1 , correspond to the coordinated carboxylic, and carbonyl groups in BDC-based MOF. Therefore, these IR spectra of modified Cu meshes also demonstrated that the carboxylate ligands were coordinated with Cu in these nanostructures grown on Cu meshes, forming CuCF meshes.…”
Section: Characterization Of Cucf Meshesmentioning
confidence: 99%
“…The photocatalytic degradation efficiencies of pesticides by novel MOFs in some recent studies are summarized in Table S1. ,,,,,, The most commonly studied pesticides in recent studies include herbicides (atrazine, ,,, 2,4-D, paraquat, 2,4-dinitrophenol (DNP)) and insecticides (diazinon, , malathion, , methyl malathion, bis­( p -nitrophenyl) phosphate (BNPP), 4-nitrophenol (4-NP), nitenpyram (NIT), and chlorpyrifos). Among them, the degradation efficiencies of atrazine are not as impressive as other pesticides, as none of the studies reported a high degradation efficiency (>90%) even after relatively long reaction time.…”
Section: Mof-catalyzed Photocatalytic Degradation Of Pesticidesmentioning
confidence: 99%
“…[ 1–3 ] On the other hand, linker and orbital engineering‐based reconstruction by incorporating pi‐conjugated ligands and intermolecular charge trapping were also explored. [ 4,5 ] The former deals with organic framework rather than the metal center, while the latter was limited only to single metal cluster. However, an approach involving intermolecular charge trapping with the assistance of two different metal centers is seen as a sensible alternative.…”
Section: Introductionmentioning
confidence: 99%